Edukasi Upaya Pencegahan Bullying Dengan Menggunakan Teknik Bimbingan Kelompok Home Room Di Lingkungan Sekolah SMK Negeri 10 Medan - Bertania Permata Sari; Fahrysyah Aulya; Adelina Sitanggang; Mira Cahya; Abdinur Batubara (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to determine the effectiveness of home room group guidance techniques in providing education and efforts to prevent bullying in the school environment at SMK Negeri 10 Medan. The method used is a qualitative method with a descriptive-analytic approach, collecting data through interviews with students and teachers, as well as observations in the school environment. The research results show that the home room group guidance technique is effective in increasing students' and teachers' understanding of bullying, as well as helping them develop the ability to overcome bullying. This technique can facilitate in-depth discussion and reflection about various forms of bullying, its impact, and prevention strategies. In addition, home room group guidance also helps build more positive relationships between students, as well as between students and teachers, thereby creating a school environment that is more conducive to preventing bullying. Thus, this research concludes that the home room group guidance technique is an effective strategy for providing education and efforts to prevent bullying in the school environment. It is hoped that this research can contribute to the development of more effective strategies in preventing bullying in schools.